College English Teaching Reform in the Era of Micro Media - Yao, Xiaochao (Journal of Theory and Practice of Social Science, 2024)
English teaching in colleges and universities is facing the situation of reform and innovation in the current era. the traditional teaching mode can no longer fit the actual situation of English teaching in colleges and universities. Therefore, the teaching mode needs to be optimized and innovated. Under the background of new era, all kinds of micro media came into the eyes of people, such as micro movie, weibo, WeChat etc, in college English teaching, can draw lessons from the media on the characteristics and advantages of teaching model reform, and helps to improve the efficiency of English teaching, micro media era is based on the present college English teaching reform has carried on the simple analysis.